Isolated Coronary Artery Anomalies- a review article - Rashid, MA; Faruque, M; Islam, AEMM; Haque, S; Rahman, AKMF; Islam, MT (University Heart Journal, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Â The term coronary artery anomaly refers to a wide range of congenital abnormalities involving the origin, course and structure of pericardial coronary arteries. By definition, these abnormalities occur in less than 1% of the general population. Coronary artery anomalies are frequently found in association with other major congenital cardiac defects. This article, however, is focused on isolated coronary artery anomalies (ie, in the absence of other major congenital cardiac defects). In adults, the clinical significance of coronary anomalies relates to their occasional association with sudden death, myocardial ischaemia, congestive heart failure, or endocarditis. In addition, presence of coronary artery anomalies may, at times, create challenges during coronary angiography, percutaneous coronary interventions, and coronary artery surgery. After hypertrophic cardiomyopathy, coronary artery abnormalities are the second most common cause of sudden death in young athletes. Â University Heart Journal Vol.4(1) January 2008 Â